Bonding durability of dental sealants to deciduous and permanent teeth - Moura, Sandra Kiss; Lemos, Letícia Vargas Freire Martins; Myszkovisk, Suellen; Provenzano, Maria Gisette Arias; Balducci, Ivan; Myaki, Silvio Issao (Faculdade de Odontologia de Piracicaba - UNICAMP, 2014)
AIM: To evaluate the bonding durability of materials used as sealants on different dentitions. METHODS: Deciduous (D) and permanent (P) molars were divided into four groups (n=5) and sealed with Fluroshield (F) and OptiBond FL (FL). Blocks of composite resin were built, stored in distilled water (24 h/37 °C), sectioned into 0.8 mm2 and tested at tensile (0.5 mm/min) after 24 h and 6 months. The fractures were observed and classified into adhesive, cohesive or mixed types. The data were analyzed using repeated measures ANOVA and Tukey test (α=5%), with tooth as the experimental unit. RESULTS: There were differences for dentition (p=0.0097), dental sealant (p=0.0019) and time (p=0.0001). At 24h the highest bond strength was observed for OptiBond FL on deciduous and permanent teeth, similar to Fluroshield at both dentitions. After 6 months the bond strength of OptiBond FL did not decrease in the permanent teeth, but decreased similar to Fluroshield in deciduous teeth, the bond strength of Fluroshield decreased similarly in both dentitions. CONCLUSIONS: The bond strength of dental sealants varied with the experimental conditions.
Keywords: dental enamel; longevity; pit and fissure sealants